The Influence of Perceived Value and Brand Experience on Purchasing Decisions of YouTube Premium Services (Study on Followers Instagram Account @Youtuber Karawang) - Anwar Musadad; Risha fatikha sari (Primanomics : Jurnal Ekonomi & Bisnis, 2023)
The study entitled " Influence Perceived Value and Brand Experience Against Purchasing Decisions YouTube Premium Service ” . aim for know influence variable Perceived Value and Brand Experience towards Purchase Decision . Population selected is follower account Instagram @YoutuberKarawang with total population as much 3700 people and from results calculation formula Isaac and Michael obtained total sample which must collected is as many as 348 people. Approach which used is quantitative, with method descriptive verification , and technique analysis path.After conducted study obtained results that Perceived values, Brands experiences, and Decision Purchase entirely get results end which good. Next results test Q variable Perceived Value (X1) and Brands Experience (X2) each own influence positive and significant in a manner Partial to variable Decision Purchase (Y). Likewise with the test results ANOVA or F test obtained results that variable Perceived Value (X1) and Brands Experience (X2) in a manner simultaneous influential to variable Purchase Decision (Y).